The high desert - Spooner, James (Harper, an imprint of HarperCollinsPublishers, 2022)
"Scene: Apple Valley, California, in the late eighties, a thirsty, miserable desert. Teenage James Spooner hates that he and his mom are back in town after years away. The one silver lining--new school, new you, right? But the few Black kids at school seem to be gangbanging, and the other kids fall on a spectrum of micro-aggressors to future Neo-Nazis. Mixed race, acutely aware of his Blackness, James doesn't know where he fits until he meets Ty, a young Black punk who introduces him to the school outsiders--skaters, unhappy young rebels, caught up in the punk groundswell sweeping the country. A haircut, a few Sex Pistols, Misfits and Black Flag records later: suddenly, James has friends, romantic prospects, and knows the difference between a bass and a guitar. But this desolate landscape hides brutal, building undercurrents: a classmate overdoses, a friend must prove himself to his white supremacist brother and the local Aryan brotherhood through a show of violence. Everything and everyone are set to collide at one of the year's biggest shows in town... Weaving in the Black roots of punk rock and a vivid interlude in the thriving eighties DIY scene in New York's East Village, this is the memoir of a budding punk, artist, and activist"--Dust jacket flap.